Pengaruh Perbedaan Metode Ekstraksi Terhadap Kadar Total Flavonoid dan Alkaloid Bonggol Buah Merah (Pandanus conoideus L.) - Innal Saitis; A.M. Muslihin; Lukman Hardia; Angga Bayu Budiyanto; Irwandi Irwandi; Marzella Dea Rossardy; Wahyuni Watora; Justitia Cahyani Fadli; Wiwit Ayu Fitrianti (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
Background: Red fruit (Pandanus conoideus L.) is an endemic plant of Papua that has been traditionally used to treat various diseases. Its biological activities are associated with the presence of secondary metabolites, particularly flavonoids and alkaloids. Objective: This study aimed to identify the secondary metabolites and evaluate the effect of different extraction methods on the total flavonoid and alkaloid contents of ethanolic extracts of red fruit (Pandanus conoideus L.) stem core. Methods: Extraction was performed using three different methods, namely maceration, Soxhlet extraction, and reflux extraction with ethanol as the solvent. Secondary metabolites were identified qualitatively, while total flavonoid and alkaloid contents were determined spectrophotometrically. Results: Phytochemical screening revealed the presence of alkaloids, flavonoids, terpenoids, steroids, and tannins in the ethanolic extract of red fruit stem core. The total flavonoid contents obtained by maceration, Soxhlet extraction, and reflux extraction were 218.966 mgQE/g (21.89%), 104.023 mgQE/g (10.40%), and 247.701 mgQE/g (24.77%), respectively. The total alkaloid contents obtained by maceration, Soxhlet extraction, and reflux extraction were 145.770 mgAE/g (14.58%), 65.767 mgAE/g (6.58%), and 76.433 mgAE/g (7.64%), respectively. Conclusion: The extraction method affected the total flavonoid and alkaloid contents obtained from the sample. Reflux extraction produced the highest total flavonoid content (247.701 mgQE/g), whereas maceration produced the highest total alkaloid content (145.770 mgAE/g). Therefore, reflux was the most effective method for flavonoid extraction, while maceration was the most effective method for alkaloid extraction from the stem core of red fruit (Pandanus conoideus L.).